Riddah dalam Perspektif Fiqh Jinayah Klasik dan Kontemporer - Mar’atul Humairah; Muhammad Wildan Nizar; Misrandiannor; Lamhudinur (Ahsan: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2025)
Riddah, or apostasy, refers to the act of a Muslim abandoning Islam after having previously accepted it. Within Islamic criminal law, riddah is categorized as an offense related to faith and the protection of religion (ḥifẓ al-dīn). This study analyzes the concept of riddah through a normative and descriptive-analytical approach by examining its legal foundations in the Qur’an, Hadith, and the interpretations of both classical and contemporary scholars. The findings show that classical jurists generally agree on the death penalty for apostasy, provided certain conditions are met, such as legal maturity, sound intellect, and the opportunity to repent (istitābah). In contrast, many contemporary scholars reinterpret the law of riddah in light of religious freedom and the objectives of Islamic law (maqāṣid al-sharī‘ah), emphasizing moral and social considerations rather than purely physical punishment. The study highlights the dominance of classical perspectives in existing research and the limited comparative analysis involving contemporary views. Therefore, a comprehensive understanding of riddah is needed to ensure that its application aligns with principles of justice, human dignity, and the overarching aims of Islamic law.